Identification of the possible new odor-active compounds "12-methyltridecanal and its analogs" responsible for the characteristic aroma of ripe Gouda-type cheese. Issue 12 (2nd December 2015) - Inagaki, Satsuki; Fujikawa, Seiji; Wada, Yoshiyuki; Kumazawa, Kenji
Abstract: The aroma concentrates of the three maturation stages of Gouda-type cheeses were prepared by combining the solvent extraction and the solvent assisted flavor evaporation techniques. The aroma extract dilution analysis applied to the volatile fraction revealed 31 odorants that were identified or tentatively identified from the 38 odor-active peaks with FD factors between 4 3 and 4 8 . By comparison with the FD factors in the three maturation stages of the cheeses, 16 odorants, including 12-methyltridecanal, which is a newly identified odorant from the cheese, increased with the increasing maturation stage of the cheese. In addition, many iso - and anteiso -methyl-branched long-chain aliphatic aldehydes could be identified as the analogs of 12-methyltridecanal, which have a unique odor note. It may be then expected that these aldehydes were able to influence the flavor of the highly ripened Gouda cheese, since these compounds also increased with the increasing maturation stage. Graphical abstract: : By comparison with the FD factors in the three maturation stages of the cheeses, 16 odorants, including 12-methyltridecanal increased with the increasing ripening.